Directing : a handbook for emerging theatre directors - Swain, Rob (Backstage., 2011)
The theatre director is one of the most critical roles in a successful drama company, yet there are no formal qualifications required for entry into this profession. This practical guide for emerging theatre directors answers all the key questions from the very beginning of your career to key stages as you establish your credentials and get professionally recognized. It analyzes the director''s role through relationships with the actors, author, designer, production manager and creative teams and provides vital advice for ""on-the-job"" situations where professional experience is invaluable. T